SONG AND VIDEO ANIMATION ON VIRUS: MULTIMEDIA TO INCREASE STUDENT'S LEARNING ACHIEVEMENT - Anggi Putri Suhadi; Khairotun Nihlah; Mieke Miarsyah; Rizhal Hendi Ristanto (Jurnal Pelita Pendidikan, 2021)
This study aimed to improve student achievement through song-based multimedia and animated videos on viral material. This type of research is (R&D) adapting the ADDIE model. The population is class X SMA IT Baitul Qurro South Tangerang, sampling using non-probability sampling with saturated sampling technique where the entire population is a sample of 45 students. Learning achievement is measured using instruments that have been validated by experts (teachers and biology lecturers) using essays (C1- C6) for cognitive tests, questionnaires for affective tests, and observation sheets for psychomotor tests. The test was conducted before (pretest) and after (posttest) learning. Data analysis used the average score, percentage, and N-gain. The data obtained were analyzed by normality and homogeneity tests. The results obtained indicate that song-based multimedia and animated videos can improve student achievement with an average N-gain, namely: Cognitive domain of 56.8% (quite effective); The affective domain is 57% (quite effective), and the psychomotor domain is 75% (quite effective).